2022
DOI: 10.3389/fnins.2022.829884
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biological Neural Networks on High Density CMOS Microelectrode Arrays

Abstract: In bottom-up neuroscience, questions on neural information processing are addressed by engineering small but reproducible biological neural networks of defined network topology in vitro. The network topology can be controlled by culturing neurons within polydimethylsiloxane (PDMS) microstructures that are combined with microelectrode arrays (MEAs) for electric access to the network. However, currently used glass MEAs are limited to 256 electrodes and pose a limitation to the spatial resolution as well as the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…Multiple methods, including laser lithography ( Schürmann et al, 2018 ), microcontact printing ( James et al, 2000 ; Nam et al, 2006 ), agarose-gel patterning ( Suzuki et al, 2005 ; Hong and Nam, 2020 ), and microfluidic devices ( Pan et al, 2015 ; Forró et al, 2018 ), have been used to pattern dissociated neurons on MEAs. Patterning dissociated neurons on HD-MEA has been demonstrated using microfluidic devices, firstly by Lewandowska et al (2015) and later by Kim et al (2020) and Duru et al (2022) . The major challenge in patterning neurons on HD-MEA devices lies in the surface topography of the device, which originates in the passivation layer and the underlying electronics, which inhibit stable sealing of the microfluidic device, as was shown in Figure 1C .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple methods, including laser lithography ( Schürmann et al, 2018 ), microcontact printing ( James et al, 2000 ; Nam et al, 2006 ), agarose-gel patterning ( Suzuki et al, 2005 ; Hong and Nam, 2020 ), and microfluidic devices ( Pan et al, 2015 ; Forró et al, 2018 ), have been used to pattern dissociated neurons on MEAs. Patterning dissociated neurons on HD-MEA has been demonstrated using microfluidic devices, firstly by Lewandowska et al (2015) and later by Kim et al (2020) and Duru et al (2022) . The major challenge in patterning neurons on HD-MEA devices lies in the surface topography of the device, which originates in the passivation layer and the underlying electronics, which inhibit stable sealing of the microfluidic device, as was shown in Figure 1C .…”
Section: Discussionmentioning
confidence: 99%
“…The studies have revealed several non-random properties such as the modular architecture as a structure that is evolutionarily conserved in the nervous system ( van den Heuvel et al, 2016 ) and provided mechanistic insights into how network structure defines system functions in both normal and pathological brains ( Lynn and Bassett, 2019 ; van den Heuvel and Sporns, 2019 ; Suárez et al, 2021 ). While many studies have deciphered the structure-function relationships in the nervous system in vivo ( Meunier et al, 2010 ; Lee et al, 2016 ), recent advances in cell engineering technology using micropatterned proteins and microfluidic devices have enabled the use of cultured cells to study these relationships in a well-defined in vitro system ( Feinerman et al, 2008 ; Lewandowska et al, 2015 ; Pan et al, 2015 ; Albers and Offenhäusser, 2016 ; Yamamoto et al, 2016b , 2018 ; Forró et al, 2018 ; Hong and Nam, 2020 , 2022 ; Takemuro et al, 2020 ; Duru et al, 2022 ; Ihle et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the current layout of the PDMS circuit is constrained by the need to interface it with a 60-electrode MEA layout and only allows recording and stimulating from specific positions in the system. By using a high-density CMOS MEA, which was recently shown to be compatible with PDMS microstructures, 73 such design constraints could be eliminated and any part of the circuits could be recorded from and stimulated. This would however complicate imaging assays, as high-density CMOS MEAs are not transparent.…”
Section: Discussionmentioning
confidence: 99%